EVALUATION OF RISK ASSESSMENT FACTORS AMONG SELECTED METALS IN ROADSIDE GROWN CEREALS OF THE SUDAN SAVANNA ECOLOGY OF NIGERIA - Anongo, M'ember Catherine; Uyovbisere, Onovosa Edwards (FUDMA JOURNAL OF SCIENCES, 2021)
Phytoaccumulation of metals (Cd, Cr, Cu, Pb, Zn) in roadside grown wheat and maize varieties ( Pavon-76, Siettecerros, Zea mays L. and Zea mays everta L.) and the toxicity and phytoremediation capability of the plants was investigated. Four sampling sites, roadside (SU 1, SU 3) and distant sites (SU 2 and SU 4) were selected by principle to represent the level of pollution near major traffic routes and were the reference sampling points. Whole plant metal levels of the four crops were determined using the multi-elemental technique- Energy Dispersive X-ray Fluorescent (EDXRF) and double beam AAS at A.B.U Zaria. Plant uptake factor (PUF), soil-plant transfer coefficient (TC) and translocation factor (TF) was computed for each metal. Pearson correlation analyses between the risk assessment factors of the metals were evaluated. Results revealed a positive significant (P<0.05) relationship between PUF/TC and PUT/TF for Cr and Zn in Pavon-76, PUF/TC for Cr and Zn in the two species of Zea mays L. and Cu in Siettecerros indicates atmospheric inputs and special ability or strong selective ability of each of the crops to accumulate certain metals. The inverse correlation between PUF/TC, PUF/TF and TC/TF among the metals indicates the proximity of SU 1 to the major highway, influence of traffic density, atmospheric inputs and geological material and a combination of other factors. This study reveals the potentialities of these varieties of Wheat and Maize which are terrestrial higher plants as accumulators of metallic elements and phytoremediators of roadside soil pollution